Controversial new religions - Lewis, James R.; Petersen, Jesper Aagaard (Oxford University Press, 2015)
In terms of public opinion, new religious movements are considered controversial for a variety of reasons. Their social organisation often runs counter to popular expectations by experimenting with communal living, alternative leadership roles, unusual economic dispositions, and new political and ethical values. As a result the general public views new religions with a mixture of curiosity, amusement, and anxiety, sustained by lavish media emphasis on oddness and tragedy rather than familiarity and lived experience. This book looks at those groups that have generated the most attention.